COMPARATIVE ANALYSIS OF MODERN CONTENT SYSTEM CONTROLS (Modern information system and technologies, 2018)
The article analyzes the most common content management systems, considers the history of each of them, as well as individual features in the development and further administration, the shortcomings and advantages of the CMS.